The effects of pin profile on joining aluminium alloy by using friction stir welding technique - Md Asyraf Zulfadhly, Md Zainudin (2013)
The main objectives of this project are to investigate the effects of tool pin profile and rotational speed towards the joint strength, hardness value, microstructural changes and defects on aluminium AA1100 welded joint. The welding process was done by using friction stir welding technique (FSW) using cylindrical tool pin and cylindrical threaded tool pin. The weld quality was evaluated by mechanical test and metallurgical analysis. Microstructural analysis was done by using optical microscope while Vickers hardness tests and tensile test was conducted to analyze the mechanical properties of weld joint. From the cross sectional area of the weld region, it is found that a wormhole defect occur throughout the weld region. The threaded pin profile produce the highest hardness value which is 68.09 HV at 1700 rpm while highest tensile strength is 113.02 MPa at 1600 rpm. The analysis from both microstructural and mechanical test shows that cylindrical threaded tool pin profile produce better weld quality compared to cylindrical pin samples.